Aspects of Apuleius' Golden Ass : Volume III: The Isis Book. a Collection of Original Papers. - Keulen, W. H. (Classical Studies E-Books Online, Collection 2012, ISBN: 9789004223240., 2011)
This new monograph on Apuleius' Isis Book not only brings together the striking diversity of opinions that continues to enliven the discussion about Book Eleven, but also sets new trends in reading the narrative in its literary, religious, archaeological and cultural context. Through a variety of approaches, including religious studies (ancient mystery cult), textual criticism, literary analysis, Greek philosophy, and archaeology, the volume sheds new light on important aspects of Book XI, such as the relation with Plutarch's De Iside et Osiride ; aspects of Lucius' multifarious physical self-presentation as an Isiac convert; aspects of style and language (wordplay), textual problems in relation to problems of interpretation; the role of Providence and Platonic philosophy, and numerous metaliterary and intertextual aspects.